Public service ethics individual and institutional responsibilities - Bowman, James S. 1945-; West, Jonathan P. 1941- (CQ Press, An Imprint of SAGE Publications, Inc., 2015)
Ethics provides the preconditions for the making of good public policy as all policies depend on it. This book builds upon the authors' teaching and research in government ethics. As a core text for upper-level undergraduate and beginning graduate students, it will examine conceptual tools to clarify moral experiences, analyze individual decision making strategies, and assess organizational ethics programs. The emphasis is not only on "how to," but also "why." The manuscript will be written in a manner accessible to academicians, students, and managers; it will to offer them practical knowledge and insight into ethics in government. To that end, the book is not about right and wrong answers. Rather it aims to understand ethics and human behavior in an analytical, yet provocative manner by ..